Magnetism in Everyday Technology: An Integrative Review of Principles, Devices, and Educational Implications - Elsiana Velsi; Tya Ratu Elizar (ISEJ : Indonesian Science Education Journal, 2024)
The advancement of science and technology has significantly transformed human life, and among the most essential phenomena underlying these developments is magnetism, which has long served as both a theoretical foundation and a practical enabler of innovation. This study employed a descriptive qualitative design through an extensive literature review of academic books, peer-reviewed journals, and reputable online resources to analyze the principles of magnetism and their applications in daily life. The findings reveal that magnetic fields are widely utilized in household devices such as refrigerators, electric bells, and loudspeakers, as well as in advanced technologies including electric motors, telecommunication systems, and medical imaging. The results further demonstrate that magnetism is not only central to technological innovation but also provides significant educational value by linking abstract concepts with real-world experiences, thereby enhancing conceptual understanding and student engagement. Comparative analysis with previous studies confirmed the reliability of these findings while highlighting the novelty of this research in synthesizing historical, theoretical, and practical dimensions into a single holistic narrative. The study implies that integrating magnetism into science curricula and leveraging its practical relevance can strengthen science literacy and foster innovation, while also underscoring the potential of magnet-based systems for advancing sustainable energy and engineering solutions.